Architecture in Support of Citizenry: Vernon DeMars and the Berkeley Student Union. Issue 2 (2nd July 2016) - Robinson, Clare
Abstract : University students perennially use college campuses for social and political protest. For this reason it is important to understand how campus design conditions student activism as well as the ways architects have worked to build spaces to practice democracy and citizenship. This article turns to the administrative policies and campus planning activities leading up to the Free Speech Movement in 1964, which took place adjacent to the postwar student union building at the University of California, Berkeley. It argues that the student center and plaza, designed by the architects Vernon DeMars and Donald Hardison and landscape architect Lawrence Halprin, gave the postwar university citizenry a monumental space to practice democracy as it paved the way for civic-oriented student centers elsewhere.